P21 Actively injecting drug users can be successfully treated with antiviral therapy for HCV, are unlikely to be re-infected, and significantly reduce their illicit drug use. (6th September 2011) - Lewis, H; Ibrahim, N; Mirza, M; Hothi, J; Wilkinson, M; Foster, G
Abstract : Introduction: Currently the predominant mode of transmission of hepatitis C virus (HCV) in the developed world is injection drug use (IDU) and HCV antibody prevalence rates reach 60–90% in those who have injected drugs. Treatment rates of injecting drug users (IDU's) with HCV are low at just 3–10% and although small studies indicate treatment of IDU's is safe and effective, data on outcomes of antiviral therapy in current injecting drug users is limited with the largest study published to date including just 31 active IDU's. It has been suggested that antiviral therapy for HCV use may reduce illicit drug use, but published data to support this is lacking Aim: To assess the treatment outcomes and the impact of antiviral therapy on illicit drug use in injecting drug users (IDU's) treated with antiviral therapy for Hepatitis C virus (HCV) by nurses based in community addiction services in North East London. The outcomes of the first 81 patients to be treated are presented here, 48 of whom were using illicit drugs at the start of treatment making this the largest cohort of active IDU's with HCV treated with antiviral therapy that has been presented to date. Method: Methods consisted of a retrospective database analysis. Illicit drug use was quantified as 3 (heavy/daily); 2 (weekly/moderate); 1 (monthly/occasional) and 0 (previous drug use). The Wilcoxon signed rank test was used for statistical analysis. Results: 81 patients were treated over a 45-month period from September 2004 to January 2009. 50 (62%) were genotype 2/3, and 31 (38%) were genotype 1. The average age of infection with HCV was 23, of diagnosis was 39 and of treatment was 41. Compliance with treatment was 88%. 63% of patients had a sustained viral response, 18% were non-responders and 10% discontinued treatment early due to side effects. 5 patients (6%) relapsed after successful treatment. Only 1 patient (1%) has been re-infected post treatment. 48 patients (60%) were actively using illicit drugs when HCV treatment was initiated. Data on pre and post treatment intravenous heroin use, crack cocaine use and alcohol use was available in 74, 40 and 21 patients respectively. Intravenous heroin use reduced from 41/74 patients (55%) to 27/74 (36%) (p=0.0033) after treatment, with daily use reducing from 16/74 (22%) to 7/74 (9%) Crack cocaine use reduced from 32/40 (80%) to 21/40 (53%) (p=0.0103) Alcohol use reduced from 15/21 (71%) to 13/21 (62%) (p=0.5775). Conclusion: Nurse led provision of antiviral therapy for HCV infected injecting drug users in community based clinics is effective, with sustained viral response (SVR) rates that compare favourably with published randomised controlled trials of pegylated interferon and ribavirin.1 High rates of compliance are seen and re-infection rates are low, so concern over compliance and re-infection should not prevent treatment of injecting drug users. This study has shown for the first time that a significant reduction in illicit drug use occurs during and after antiviral therapy demonstrating a social benefit of treatment in addition to the known health benefits.